Wisata Edukasi Hasil Aktifitas Gunung Api Purba Pada Bekas Tambang di Desa Hargorejo, Kecamatan Kokap, Kabupaten Kulon Progo - Amara Nugraheni; R. Bagus Ugra W (Retii, 2020)
Pole stumps in frozen rock in Hargorejo Village, Kokap District, Kulon Progo Regency, Yogyakarta Special Region is one of the natural formations that have a beauty formed due to the rise of magma to the earth's surface. One of the typical landscape objects, namely the hill, the former volcanic activity with a fairly wide distribution. Based on the lithological analysis that has been carried out, it shows that the igneous rock hills are located in hilly areas with high elevations and ramps.This study aims to determine how much tourism development as an attraction for "Educational Tourism" in Kulon Progo Regency which can be developed to improve the welfare of the community. This study uses a qualitative descriptive research method with reference to the concept of educational tourism and tourism development. The results showed that the development of tourism in the former mining location of igneous andesite rocks in the form of sturdy poles as a form of educational tourism development as a natural tourism that highlights the beauty, uniqueness, rarity and magic of a natural phenomenon related to geological symptoms that make this area has a beautiful view and has the potential as an object of educational tourism.